2016
DOI: 10.1523/jneurosci.0636-16.2016
|View full text |Cite
|
Sign up to set email alerts
|

A New Glucocerebrosidase Chaperone Reduces  -Synuclein and Glycolipid Levels in iPSC-Derived Dopaminergic Neurons from Patients with Gaucher Disease and Parkinsonism

Abstract: Among the known genetic risk factors for Parkinson disease, mutations in GBA1, the gene responsible for the lysosomal disorder Gaucher disease, are the most common. This genetic link has directed attention to the role of the lysosome in the pathogenesis of parkinsonism. To study how glucocerebrosidase impacts parkinsonism and to evaluate new therapeutics, we generated induced human pluripotent stem cells from four patients with Type 1 (non-neuronopathic) Gaucher disease, two with and two without parkinsonism, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
179
0
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 205 publications
(184 citation statements)
references
References 34 publications
1
179
0
4
Order By: Relevance
“…Aged neurons from the subjects with PD recapitulate the patient phenotype by displaying increased α-syn levels. This work also demonstrated that iPSC-dopaminergic neurons from patients with type 2 GD, the most severe acute neuronopathic form, also show increased α-syn accumulation (Aflaki et al, 2016). …”
Section: Insights From New Modelsmentioning
confidence: 67%
See 2 more Smart Citations
“…Aged neurons from the subjects with PD recapitulate the patient phenotype by displaying increased α-syn levels. This work also demonstrated that iPSC-dopaminergic neurons from patients with type 2 GD, the most severe acute neuronopathic form, also show increased α-syn accumulation (Aflaki et al, 2016). …”
Section: Insights From New Modelsmentioning
confidence: 67%
“…It was also found that infants with type 2 GD disease who often have extremely low residual GCase activity exhibit increased neuronal α-syn levels (Aflaki et al, 2016; Mazzulli et al, 2011), although no α-syn pathology is noted at autopsy (Berger-Sieczkowski et al, 2016). …”
Section: Biological Relationshipsmentioning
confidence: 99%
See 1 more Smart Citation
“…A number of investigations into the use of gene therapy to augment GCase levels in GBAmutation carrying models and models of PD, through adeno-associated virus-mediated (AAV-mediated) expression of GCase in the CNS via cerebral injections has found hugely beneficial effects [88,89], which serves as an excellent proof of concept for the use of GCase activity augmentation in the reduction of alpha-synuclein accumulation and transmission [89,90], and neurodegeneration in PD models [88], which will be an avenue to pursue further with a view to translation to human PD patients.…”
Section: Gcase As a Therapeutic Targetmentioning
confidence: 99%
“…Initially, it was proposed that the proteasome degraded alpha-synuclein. However, recent studies showed that alpha-synuclein is preferentially degraded via lysosomes, especially with protein overexpression (Aflaki et al, 2016;Mak et al, 2010).…”
Section: Resultsmentioning
confidence: 99%